Real-time ligand binding of fluorescent VEGF-A isoforms that discriminate between VEGFR2 and NRP1 in living cells - Peach, Chloe J.; Kilpatrick, Laura E.; Friedman-Ohana, Rachel; Zimmerman, Kris; Robers, Matthew B.; Wood, Keith V.; Woolard, Jeanette; Hill, Stephen J. (Elsevier, 2018)
Fluorescent VEGF-A isoforms have been evaluated for their ability to discriminate between VEGFR2 and NRP1 in real-time ligand binding studies in live cells using BRET. To enable this, single-site (N-terminal cysteine) labelled versions of VEGF165a, VEGF165b and VEGF121a were synthesised. These were used in combination with N-terminal NanoLuc-tagged VEGFR2 or NRP1 to evaluate the selectivity of VEGF isoforms for these two membrane proteins. All fluorescent VEGF-A isoforms displayed high affinity for VEGFR2. Only VEGF165a-TMR bound to NanoLuc- NRP1 with a similar high affinity (4.4nM). Competition NRP1 binding experiments yielded a rank order of potency of VEGF165a > VEGF189a > VEGF145a. VEGF165b, VEGF-Ax, VEGF121a and VEGF111a were unable to bind to NRP1. There were marked differences in the kinetic binding profiles of VEGF165a-TMR for NRP1 and VEGFR2. These data emphasise the importance of the kinetic aspects of ligand binding to VEGFR2 and its co-receptors in the dynamics of VEGF signalling.